STUDY OF A NON-TOXIC PERFLUORINATED SURFACTANT ACTIVE IN ANTIFOULING BY THE OPTICAL POLARIZING MICROSCOPE (OPM) AND BY IMAGEJ - BACHA, A.; MEGHABAR, R. (Courrier du Savoir; Vol 23 (2017): COURRIER DU SAVOIR (JUIN), 2017)
The incorporation of fluorinated carbon atoms in a chain is a simple process in polymers to improve the ability to protect against atmospheric corrosion coatings, and thanks to their low surface tension, no water wettability and oil and antifouling properties. To this end, we synthesized a surfactant perfluorinated based on acrylic acid (monomer). The composition of the surfactant used is determined by nuclear magnetic resonance (1H NMR) and Steric Exclusion Chromatography (SEC). The aggregation of this telomere characteristics were examined by the Optical Microscope Polarizer (MOP), and the signal processing software imagJ.